Explaining Religio-Political Tolerance Among Muslims: Evidence from Indonesia - Mujani, Saiful (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2019)
Once a fully free country according to Freedom House, Indonesia has declined to partly free in the last seven years, indicating that the largest Muslim democracy in the world is deconsolidating. The decrease of freedom in Indonesia is believed to be associated with intolerance toward religious minorities, specifically by Muslims toward non-Muslims. Previous studies found that Indonesians are in general intolerant. However, those studies ignore factors which have the potential to strengthen religio-polititical tolerance. My contribution is to fill this empty space by explaining the intolerance. The potential explanatory factors are political, economic, and security conditions, institutional engagement, political engagement, and democratic values. Based on a nationwide public opinion survey, this study reveals new findings about which factors are more crucial to strengthening religio-political tolerance. Muslim religiosity affects significantly and negatively religio-political tolerance. However, economic, political, and security conditions, institutional engagement, political engagement, democratic values, and Javanese ethnicity more significantly explain the tolerance. If these factors prevail over religion and religiosity, tolerance will improve.